RESPONSE OF HEMOMICROCIRCULATORY BED OF INTERNAL ORGANS ON VARIOUS EXTERNAL FACTORS EXPOSURE BASED ON THE MORPHOLOGICAL RESEARCH DATA - Pronina, O.M.; Koptev, M.M.; Bilash, S.M.; Yeroshenko, G.A. (World of Medicine and Biology, 2018)
The analysis of recent scientific studies regarding the issues of morphological changes in the hemomicrocirculatory bed in response to various external factors exposure was carried out. Morphological research was carried out on 40 white male Wistar rats with body weight 240-260 grams, aged 8-10 months; 20 rats were exposed to acute stress (group 1), and 20 animals were included to the control group. The hemomicrocirculatory bed is extremely sensitive to the influence of various factors, which responds to the development of specific or nonspecific reactions. The similar morphological changes occur in the hemomicrocirculatory bed of various internal organs under the influence of acute stress, which indicates their nonspecificity.